(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The fantasy genre has gained popularity and influence in world literature, including Uzbek literature. Authors in Uzbek literature have embraced elements of magic, folklore, and fantastical storytelling, creating captivating realms that allow readers to embark on extraordinary journeys through the realms of imagination. Fantasy literature often involves the presence of magic, which shapes the narrative and adds wonder and enchantment. It also explores themes of light and darkness, creating a moral and ethical framework. Fantasy worlds can take various forms and may be based on different time periods or alternate realities. In Uzbek literature, the genre has seen growth with authors like Mahkam Mahmudov, Murad Khidir, and others contributing to the genre. The fantasy genre allows authors and readers to explore limitless possibilities and escape the constraints of reality, immersing themselves in enchanting and imaginative realm